Impact of nutrient management based on soil test data on biomass production and partitioning and growth indices of short-duration cassava (Manihot esculenta) - SUJA, G; JOHN, K SUSAN; SREEKUMAR, J (The Indian Journal of Agricultural Sciences, 2011)
Field experiments were conducted during 2004–07 at Thiruvananthapuram, Kerala, in a lowland situation similar to rice fallow to standardize the nutrient management practices for short-duration cassava (Manihot esculenta Crantz). The phasic pattern of biomass production and partitioning and growth indices of 5 short-duration/early bulking cassava lines (‘Vellayani Hraswa’, ‘Kalpaka’, ‘Sree Jaya’, ‘Sree Vijaya’ and ‘Triploid 2-18’) was studied under four levels of fertility (full farmyard manure+ NPK, 75% farmyard manure + NPK, 50% farmyard manure + NPK and based on soil test data). ‘Triploid 2-18’ and ‘Vellayani Hraswa’ had appreciably higher total biomass (1371.5 and 1264.7 g/plant), tuber biomass (857.3 and 826.0 g/plant), crop growth rate (15.95 and 14.82 g/m2/day), tuber bulking rate (10.111 and 9.365 g/day), mean tuber bulking rate (4.763 and 4.590 g/day) and harvest index (0.63 and 0.65). Nutrient management based on soil test data promoted biomass production and partitioning to tubers, crop growth rate, tuber bulking rate and harvest index at par with that of full farmyard manure + NPK, saving the entire quantity of P, 10% N and 15% K (farmyard manure 12.5 tonnes/ha and NPK 90:0:85 kg/ha) by the third year.